A Meta-Analytic Review of Tactile-Cued Self-Monitoring Interventions Used by Students in Educational Settings - McDougall, Dennis; Ornelles, Cecily; Mersberg, Kawika; Amona, Kekama (Journal of the American Academy of Special Education Professionals, 2015)
In this meta-analytic review, we critically evaluate procedures and outcomes from nine intervention studies in which students used tactile-cued self-monitoring in educational settings. Findings suggest that most tactile-cued self-monitoring interventions have moderate to strong effects, have emerged only recently, and have not yet achieved the evidence-based status of audio-cued and visual-cued self-monitoring. At present, tactile-cued self-monitoring is a promising practice with the potential to promote a variety of outcomes in educational settings. We also identify strengths and limitations of tactile-cued self-monitoring studies, provide recommendations for future research and practice, identify limitations of this analytic literature review, and list resources for researchers and practitioners.